2014
DOI: 10.1016/j.virol.2014.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of multiple conserved nuclear localization signals within adenovirus E1A

Abstract: The human adenovirus 5 (HAdV-5) E1A protein has a well defined canonical nuclear localization signal (NLS) located at its C-terminus. We used a genetic assay in the yeast Saccharomyces cerevisiae to demonstrate that the canonical NLS is present and functional in the E1A proteins of each of the six HAdV species. This assay also detects a previously described non-canonical NLS within conserved region 3 and a novel active NLS within the N-terminal/conserved region 1 portion of HAdV-5 E1A. These activities were al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Even with having substantial differences in primary sequence, E1A proteins are often remarkably consistent in their functional similarities (33). Our findings establish that 5 representative members of the 7 species of HAdV express E1A proteins that make protein-protein interactions with PKA.…”
Section: Discussionmentioning
confidence: 52%
“…Even with having substantial differences in primary sequence, E1A proteins are often remarkably consistent in their functional similarities (33). Our findings establish that 5 representative members of the 7 species of HAdV express E1A proteins that make protein-protein interactions with PKA.…”
Section: Discussionmentioning
confidence: 52%
“…E1A has previously been reported to contain a second nuclear localization signal (NLS) within the first exon of the gene [29]. We therefore wanted to determine whether deletions within this exon affect the sub-cellular localization of E1A while its strong C-terminal NLS remains intact during viral infection.…”
Section: Deletions Within Exon 1 Of E1a Do Not Affect Its Sub-cellulamentioning
confidence: 99%
“…Several studies have found that alterations in protein localization can affect cell function (16,17). The occurrence of tumors may be associated with the abnormal localization of proteins; therefore, it was hypothesized that alterations in protein location were also implicated in the pathogenesis of APL.…”
Section: Discussionmentioning
confidence: 99%